2018
DOI: 10.1016/j.jaci.2017.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Obese asthmatic patients have decreased surfactant protein A levels: Mechanisms and implications

Abstract: SP-A functions as an important mediator in resolving tissue and lavage fluid eosinophilia in allergic mouse models. Decreased levels of SP-A in OAs, which could be due to increased local TNF-α levels, might lead to impaired eosinophil resolution and could contribute to the eosinophilic asthma phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 39 publications
(40 reference statements)
0
39
0
1
Order By: Relevance
“…Some studies have shown that increased leptin levels in obese adolescents correlate inversely with FEV1, FVC, and the FEV1/FVC ratio and that visceral fat leptin expression correlates with airway reactivity in adults. Leptin, along with adiponectin, has also been linked to exercise-induced changes in lung function [52][53][54][55][56][57].…”
Section: Pulmonary Systemmentioning
confidence: 99%
“…Some studies have shown that increased leptin levels in obese adolescents correlate inversely with FEV1, FVC, and the FEV1/FVC ratio and that visceral fat leptin expression correlates with airway reactivity in adults. Leptin, along with adiponectin, has also been linked to exercise-induced changes in lung function [52][53][54][55][56][57].…”
Section: Pulmonary Systemmentioning
confidence: 99%
“…Therapies that aim to minimize eosinophilic inflammation aid in the reduction of symptoms associated with allergic airway disease (14). In addition, studies have shown that obese asthmatics have more severe tissue eosinophilia (15,16) and that they also have decreased levels of SP-A compared with lean normal and lean asthmatic individuals (17). Moreover, in a mouse model of allergic airway inflammation, administration of exogenous SP-A promoted the resolution of tissue eosinophilia (17).…”
mentioning
confidence: 99%
“…Additionally, obese asthmatics have been shown to have higher tissue eosinophilia compared to non-obese asthmatics [ 26 , 27 ]. In support of these findings, using allergic mouse models in mice lacking SP-A (SP-A −/− ), we discovered SP-A −/− mice had more severe tissue eosinophilia compared to wild-type mice which was resolved upon treatment with exogenous SP-A [ 25 ].…”
Section: Sp-a and Asthmamentioning
confidence: 85%
“…All data thus far from the field have suggested that an adequate pool of functional SP-A is a necessary contributor for normal lung function, whether during periods of homeostasis, infection or allergen challenge. Decreased levels of SP-A as seen in obese asthmatics [ 25 ] or dysfunctional SP-A as detected in some asthmatics [ 24 ], have both been associated with altered lung function and may result in enhanced airway inflammation in asthma. We provide evidence that genetic variation within SP-A2 alters the ability of SP-A to inhibit eosinophil EPO release, which could lead to worse asthma exacerbations upon pathogen infection in those asthmatics harbouring the minor allele (223K).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation